First principles simulations of mangiferin interacting with beta-cyclodextrin - Vendrame, Laura; Bonorino, Fabio; Carmo, Guilherme do; Madalosso, Rodrigo; Raffin, Renata Platcheck; Gomes, Patrícia; Fagan, Solange Binotto (Disciplinarum Scientia | Naturais e Tecnológicas, 2017)
The structural and electronic properties of the mangiferin molecule interacting with the molecule beta-cyclodextrin (beta-CD) are investigated. In this work we used ab initio calculations using the SIESTA Code. The results show a weak interaction of mangiferin molecules when absorbed on the external fragment and a stronger interaction when introduced at beta-CD’s cavity. These adsorptions cause minor changes on the electronic structure, making the weak interaction interesting in the chemical and biological point of view. In this work the interaction of beta-CD with mangiferin molecule was performed through ab initio simulations using the SIESTA Code. The complex between mangiferin and beta-CD is kept associated without altering the structural properties of the drug with original active principles, thus indicating that it can be removed from beta-CD.